2014
DOI: 10.1094/pdis-05-14-0481-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Lettuce Chlorotic Leaf Rot Disease Caused by Phytoplasma in China

Abstract: Lettuce (Lactuca sativa) as annual or biennial crop is an important vegetable in China. The lettuce variety Feiqiao, which is extensively cultivated in autumn and winter, is grown for its stem and is a characteristic species bred in Yong'an City. Since October 2005, a new disease of lettuce has been observed sporadically in the fields. Initially, chlorotic symptoms, or a faded red color, were observed on the inner leaves of the infected lettuce plants. Then, the inner leaves bleached and appeared pale, while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Previously, Lin et al (2014) stated that chlorotic symptoms or a faded red colour were reported on the inner leaves of phytoplasmainfected lettuce plants in China. They also stated that the inner leaves were bleached and gummosis was visible at the base of young leaves, and the whole plant became stunted and died.…”
mentioning
confidence: 99%
“…Previously, Lin et al (2014) stated that chlorotic symptoms or a faded red colour were reported on the inner leaves of phytoplasmainfected lettuce plants in China. They also stated that the inner leaves were bleached and gummosis was visible at the base of young leaves, and the whole plant became stunted and died.…”
mentioning
confidence: 99%
“…Phytoplasmas affect plant species which mostly belong to Apiaceae, Asteraceae, Cucurbitaceae, Fabaceae and Solanaceae families from those 16 different ribosomal groups have been reported worldwide in 16SrI-A, 16SrI-B, 16SrIII-J, 16SrIX and 16SrXII-A (Kumari et al, 2019). For example, Lin et al (2014) reported that Ca. P. asteris (16SrI) was associated with the most common symptoms such as chlorosis and wilting on infected lettuce plants were.…”
Section: Introductionmentioning
confidence: 99%